The Effect of Statins in Combination with Chemotherapy on Colon Cancer Cell Lines - A Hedayatizadeh-Omran; F Hasani; M Saeedi; R Shekarriz; M Ahmadi; P Ebrahimnejad; R Alizadeh-Navaei (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2022)
Background and Objective: Considering the anti-cancer effects of statins on colon cancer previously reported in epidemiological studies and uncertainty about the mechanisms of action, this study was performed to investigate the effect of statins in combination with chemotherapy on colon cancer cell lines. Methods: The present study, which is a laboratory study, was performed on HT-29 cell line as colon cancer cell line and normal HFF cell line. After cell culture, atorvastatin at doses of 15 and 30 μM, rosuvastatin at doses of 30 and 60 μM, simvastatin at doses of 10 and 20 μM and 5-fluorouracil (5-FU) at 20 μg/ml were used for interventions in this study. Interventions were performed alone and in combination. Finally, MTT test was performed to evaluate cell viability. Findings: Mean cell viability in simvastatin (20 μM) and simvastatin (20 μM)+5-FU (20 μg/ml) on colorectal cancer cell lines was 58.46±7.58 and 55.73±15.33 (p=0.999), respectively, in rosuvastatin (30 μM) and rosuvastatin (30 μM)+5-FU (20 μg/ml) was 91.63±10.3 and 56.2±10.27 (p=0.026), respectively, and in atorvastatin (30 μM) and atorvastatin (30 μM)+5-FU (20 μg/ml) was 82.3±26.9 and 52.16±9.49 (p=0.24), respectively. Conclusion: The evaluation of cell proliferation showed that the addition of rosuvastatin to standard chemotherapy, unlike atorvastatin and simvastatin, had an increasing effect on cytotoxicity.